Kebijakan Publik Perlindungan Lahan Pertanian Di Kabupaten Batang :Analisis Teori David Easton - Ihsan Wira Senjaya (UNISSULA Semarang, 2020)
Agricultural land has a role and function as a basic resource in land-based agriculture. The erosion of agricultural lands by human activities causes the conversion of agricultural land into non-farms is increasing. The Birth of Batang Regency Regulation Number 7 Year 2011 About Spatial Planning of Batang Regency Year 2011-2031 has led to the potential of land conversion to non-agriculture. finally the Office of Agriculture Crops and Animal Husbandry draft proposes and develops a policy of Regent Regulation to prevent the transfer of land functions. Through the analysis of David Easton System Theory obtained a scheme of policy models that occurred in Batang District related to the protection of agricultural land. The Regent's Regulation has produced feedback and new inputs to give birth to the revision of Regional Regulation of Spatial Plan of Batang Regency. Keywords: Agricultural Land, David Easton Theory